Cross-cultural comparison of fundamental movement skills in 9- to 10-year-old children from England and China. (May 2022) - Ma, Jiani; Duncan, Michael J.; Chen, Si-Tong; Eyre, Emma L.J.; Cai, Yujun
The present study aimed to examine cross-cultural differences in fundamental movement skills (FMS) proficiency levels in children aged 9–10 years old in England and China, using a process-oriented FMS measurement. Four FMS (run, jump, throw, catch) were measured using the Test of Gross Motor Development-2 (TGMD-2). The sample consisted of 272 (58.3% boys, 41.7% girls) Chinese children and 273 (48.7% boys, 51.3% girls) English children. ANCOVA analysis for the raw FMS scores showed significant sex by country interaction ( P = .022, partial η 2 = .01). Chinese children scored higher than English children on total FMS, locomotor, and object control skill subsets. Additional Chi-squared analyses revealed significant differences regarding mastery levels of skills, with a higher proportion of Chinese children being classified as having advanced skill proficiency across three of four selected FMS (i.e. run, throw, and catch). The substantial cross-cultural differences found may be related to aspects such as Physical Education (PE) provision and process, educational policy, and other physical activity opportunities (e.g. extracurricular organised sports). Our findings require further examination of the contextual influences, in order to understand the optimal strategies that promote children's FMS development through PE, youth sports, or physical activity promotion.